The Roles of Vehicle Currency and Real Effective Exchange Rates in the Trade of Every ASEAN Member With the EU-28 - Ho Hoang Gia Bao; Hoang Phong Le (SAGE Open, 2022)
A common limitation of the studies on the exchange rate-trade balance linkage is ignoring the USD’s role as a vehicle currency. Some recent papers have recognized this gap and proposed a hypothesis that the neglection of the USD’s role as a vehicle currency can restrict the significance of findings. This study aims to test that hypothesis in the trade between each of the 10 countries in ASEAN (Association of Southeast Asian Nations) with the whole EU-28. Specifically, this paper is the first to examine how the vehicle currency USD’s exchange rates, along with the real effect exchange rates, asymmetrically impact the trade balance of each ASEAN country with the EU-28 by employing the NARDL method to investigate whether the ignorance of the USD leads to fewer significant coefficients of exchange rates. The results indicate that the vehicle currency model (VCER) outperforms the real effective exchange rate (REER) model, which supports the hypothesis. In addition, the results are robust when controlling for the role of exchange rate volatility.